Accurate measurement of thin film mechanical properties using nanoindentation - Zak, S.; Trost, C. O. W.; Kreiml, P.; Cordill, M. J. (Journal of materials research, 2022)
For decades, nanoindentation has been used for measuring mechanical properties of films with the widely used assumption that if the indentation depth does not exceed 10% of the film thickness, the substrate influence is negligible. The 10% rule was originally deduced for much thicker metallic films on steel substrates and involved only the hardness measurement. Thus, the boundaries of usability for measuring thin film elastic modulus may differ. Two known material systems of Mo and MoTa thin films on Si substrates are examined with nanoindentation and numerical modeling to show the limitations in measuring elastic moduli. An assessment of the hardness and elastic modulus as a function of contact depth and accurate modeling of the film/substrate deformation confirms the 10% rule for hardness measurements. For elastic modulus, the indentation depths should be much smaller. Results provide a recommended testing protocol for accurate assessment of thin film elastic modulus using nanoindentation. Graphical abstract